Pengaruh Komunikasi Antarpribadi Bermedia Internet terhadap Persahabatan Mahasiswa di Dunia Maya - Anne Ratnasari (MediaTor (Jurnal Komunikasi), 2007)
The problem which was studied is the influence of the Internet mediated interpersonal communication on online student friendship. Some communication modes are available on the Internet however this research focused on the use of chat facility to establish student online friendship. The quantitative aproach was applied by conducting explanatory survey method to determine the influence of the Internet mediated interpersonal communication through Chatting on student online friendship. Some aspects which were studied on this research are Chatting intensity, Chatting appeal, Chatting dependency, and communication messages while Chatting. All those aspects were considered their influence on student online friendship. Population of this research is students who used chat facility in the Kubus Net Bandung. The data of this research was analyzed using path analysis to determine the level of influence of each research variable. The result of influence test on the four hypothesis either partially or simultaneously showed that there was an influence of Chatting intencity, Chatting appeal, Chatting dependency, and communication messages while Chatting on the student online friendship of the student who use chat facility. The four aspects of Chatting influence differently on student online friendship. Chatting message had more influence than Chatting intensity, dependency and Chatting appeal to the student online friendship.